UTERUS PRESERVING TREATMENT MODALITIES FOR ABNORMAL INVASIVE PLACENTA: A SYSTEMATIC REVIEW - Syahputra Damanik, Roni Andre (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
All medical personnel who provide care for pregnant women face a challenge in diagnosing and treating abnormal placentation since it displays a unique set of symptoms. The direct attachment of placental villi to the myometrium, with the risk of further invasion into the uterine wall or surrounding organs, is one of the leading causes of postpartum hemorrhage. Aberrant placentation is defined by this direct attachment of placental villi to the myometrium. It has been determined that primary risk factors for placenta accreta include surgical procedures that damage uterine integrity. These operations include cesarean section, dilatation and curettage, and myomectomy. When a focal accreta is identified, conservative treatments, such as preserving the uterus and placenta and then undergoing methotrexate therapy or pelvic artery embolization, may be explored. Despite this, surgical management is still the gold standard for treating the condition. Due to the intricacy of surgery, conservative management should be reserved for individuals who are interested in preserving their fertility as well as those who have major disease.